2023
DOI: 10.1371/journal.pmed.1004175
|View full text |Cite
|
Sign up to set email alerts
|

Institutional dashboards on clinical trial transparency for University Medical Centers: A case study

Abstract: Background University Medical Centers (UMCs) must do their part for clinical trial transparency by fostering practices such as prospective registration, timely results reporting, and open access. However, research institutions are often unaware of their performance on these practices. Baseline assessments of these practices would highlight where there is room for change and empower UMCs to support improvement. We performed a status quo analysis of established clinical trial registration and reporting practices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…The report cards require a structured trial transparency dataset, i.e., a dataset of clinical trials and their performance across several transparency practices. We previously developed methods to assess transparency practices for a cohort of trials using a combination of automated and manual approaches, which are described in detail elsewhere (Franzen et al, 2023; Franzen, 2023; Riedel et al, 2022; Salholz-Hillel et al, 2022). Supplement 4 summarizes the main steps to prepare a trial transparency dataset for use with the report cards.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The report cards require a structured trial transparency dataset, i.e., a dataset of clinical trials and their performance across several transparency practices. We previously developed methods to assess transparency practices for a cohort of trials using a combination of automated and manual approaches, which are described in detail elsewhere (Franzen et al, 2023; Franzen, 2023; Riedel et al, 2022; Salholz-Hillel et al, 2022). Supplement 4 summarizes the main steps to prepare a trial transparency dataset for use with the report cards.…”
Section: Methodsmentioning
confidence: 99%
“…In turn, the French Open Science Monitor shows the evolution at the national level of several open science practices, such as open access and mentions of data sharing in publications (Jeangirard, 2019). These initiatives and others (Barbers et al, 2022; Diprose et al, 2023; Franzen et al, 2023; QUEST Center for Responsible Research, Berlin Institute of Health at Charité Universitätsmedizin Berlin, n.d.) provide baseline information against which change can be measured and empower efforts to drive research transparency.…”
Section: Introductionmentioning
confidence: 99%
“…Research waste and late publishing of randomised clinical trials are areas that have received increased focus as of late [3]. A recent study of German University Medical Centers found that prospective registration of interventional trials, within all therapeutic areas, had increased from 33% to 75% between 2009 and 2017 in ClinicalTrials.gov.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study of German University Medical Centers found that prospective registration of interventional trials, within all therapeutic areas, had increased from 33% to 75% between 2009 and 2017 in ClinicalTrials.gov. However, only 41% of included trials had published their result within 2 years of trial completion and 31% had not published their result even after 5 years of trial completion [3].…”
Section: Introductionmentioning
confidence: 99%
“…The proportion of clinical trials reporting their results in timely manner can be monitored with tools such as the FDAAA Trials Tracker (7) for trials initiated in the USA, or the EU Trials Tracker (8) for trials initiated in the European Union. Although there has been improvement, with an increase from 50% in 2018 to 84% in late 2022 (9), communication of results either by posting results on registries or by publications remains suboptimal (10) (11). The lowest proportions are observed for academic sponsors (12), with some heterogeneity across countries, with France registering among the lowest proportions (13).…”
Section: Introductionmentioning
confidence: 99%